Elevated circulating group-2 innate lymphoid cells expressing activation markers and correlated tryptase AB1 levels in active ascariasis - López, Juan-Felipe; Zakzuk, Josefina; Satitsuksanoa, Pattraporn; Lozano, Ana; Buergi, Laura; Heider, Anja; Alvarado-Gonzalez, Juan Carlos; Babayev, Huseyn; Akdis, Cezmi; van de Veen, Willem; Caraballo, Luis; Akdis, Mübeccel (Frontiers in Immunology, 2024)
Introduction: Ascaris lumbricoides infection is one of the most common soil-transmitted helminthiasis and, IgE response to this helminth may increase the risk of asthma, bronchial hyperreactivity and atopy. There is not enough evidence showing the role of type-2 innate lymphoid cells (ILC2) in the pathogenesis of helminth infections in humans. Here, we aimed to investigate and characterize the influence of Ascaris lumbricoides infection on circulating ILCs in endemically exposed subjects. Methods: Non-infected (NI; n=16) and Ascaris-infected (AI; n=16) subjects from an endemic area were included. Two consecutive stool samples from each subject were examined by Kato-Katz to define parasite infection. Antibodies to the ABA-1 antigen of Ascaris and Ascaris extract were measured by ELISA. ILC subsets and their activation markers (CD25, CD69, thymic stromal lymphopoietin receptor (TSLPR) and NKp44) were evaluated in PMBC by flow cytometry. Proximity extension assay (PEA) was performed to explore plasma proteins associated to infection. Results: No significant differences in the relative or absolute frequencies of total ILCs, ILC1, ILC2 and ILC3 cells were observed regarding the infection status. However, within AI group, IgE-sensitized subjects to ABA-1 had higher frequencies and counts of ILC2 (p<0.05). Frequencies of CD25+, CD69+ and TSLPR+ ILC2 were higher in AI compared to the NI (p<0.01). Additionally, egg burden was positively correlated with CD69+ ILC2 frequencies (r=0.67; p=0.005). Tryptase alpha/beta 1 (TPSAB1), GP6 and several plasma proteins associated with cell growth and granulocyte chemotaxis were highly expressed in the AI group (p<0.05). Interestingly, TPSAB1 levels were positively correlated with activated-ILC2 frequencies, egg burden and IgE levels against Ascaris. Discussion: Ascaris infection is associated with increased expression of ILC2 activation markers and TPSAB1, which may contribute to the type-2 response.